NC-SC functional gradient compression-resistant material with undamaged interface and preparation method of NC-SC functional gradient compression-resistant material

By adopting the design of gradient layer structure in functional gradient compressive materials, the problem of easy destruction of the interface of functional gradient materials is solved, and efficient material utilization and cost reduction are achieved.

CN119748594APending Publication Date: 2025-04-04FUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311716302.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing functional gradient materials are prone to sudden cracks in the interface, which cannot effectively solve the problem of interface damage when ordinary concrete and self-healing concrete are combined.

Method used

Using the design method of functional gradient compressive materials, ordinary concrete and self-healing concrete are combined in different volume ratios to form a gradient layer structure. The thickness of each layer is equal, and the volume fraction of SC material changes gradiently, thereby eliminating the weak area of ​​the interface and achieving mutual coordination of strains between layers.

Benefits of technology

The interface is not damaged, and the material still has the high ductility and crack control capabilities of self-healing concrete, making full use of material properties, avoiding resource waste and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119748594A_ABST
    Figure CN119748594A_ABST
Patent Text Reader

Abstract

The invention discloses an NC-SC functionally graded compressive material with an interface not damaged and a preparation method thereof, the functionally graded material comprises an NC material and an SC material, and the NC material and the SC material are in gradient change according to the volume fraction of the SC material to form different layers. The concept of functional gradient is introduced, the NC material and the SC material serve as basic phases and are compounded according to different volume ratios, the volume fraction of the SC material is taken as a main part, and the volume fraction of the SC material is changed in a gradient mode, so that different gradient layers are formed. When NC-SC functionally graded materials with different volume fractions are combined in a layered mode, weak interface areas can be eliminated, interlaminar strain coordination can be achieved, the NC-SC functionally graded materials still have the high ductility and crack control capacity of SC, the materials are fully utilized, resource waste is avoided, a large amount of cost is saved, and the NC-SC functionally graded materials have good application prospects. And the method has a wide application prospect in engineering construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material design, and in particular to a NC-SC functional gradient compression-resistant material with an interface that is not damaged and a preparation method thereof. Background Art

[0002] Normal Concrete (NC) is widely used in various infrastructure constructions due to its advantages of high compressive strength, abundant raw materials, low price, and simple process. However, it has disadvantages such as high brittleness, poor toughness, low tensile strength, and difficulty in controlling the width of cracks after cracking. At the same time, accompanied by the harsh effects of the natural environment, it will cause a series of problems such as carbonization reaction, alkali-aggregate reaction, and corrosion damage to the components, resulting in huge testing and maintenance costs. Therefore, it is very meaningful to develop a new material with crack control capabilities.

[0003] Self-healing concrete (SC) has the ability to heal cracks, but due to its high cost, it cannot be used on a large scale in engineering. If NC and SC are combined, it is particularly important to fully utilize the two materials while reducing the cost. However, directly combining NC and SC to form an ordinary composite material will cause obvious local stress concentration due to the sudden change in material composition and performance, which will cause sudden cracking at the interface.

[0004] Therefore, how to use NC and SC as basic materials to develop a NC-SC functional gradient compressive material with no interface damage has great application prospects. Summary of the invention

[0005] In order to solve the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a NC-SC functional gradient compressive material with no interface damage and a preparation method thereof, so as to solve the problem that the existing functional gradient materials are prone to sudden cracking at the interface.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: providing a NC-SC functional gradient compressive material with no interface damage, the material comprising: NC material and SC material, the NC material and the SC material form different layers in a gradient manner according to the volume fraction of the SC material, and the thickness of each layer is equal.

[0007] The beneficial effects of adopting the above technical solution are as follows: Functionally Graded Materials (FGM) is a concept inspired by the gradient structure in nature (bamboo stems, teeth, bones, etc.). Compared with uniform materials and simple composite materials, its advantages mainly lie in the structural composition. The principle is to gradually composite two or more materials with different properties in the structure. The components of the composited materials change evenly with the structure, and there is no obvious interface inside. The performance of the material changes slowly with the change of the composition and structure of the material, thereby presenting the effect of gradient function.

[0008] The present invention introduces the concept of functional gradient, and uses ordinary concrete NC and self-healing concrete SC as basic materials. The two are compounded in different volume ratios, with the volume fraction of SC material as the main material. The volume fraction of the SC material changes in a gradient to form different layers, each layer can be called a gradient layer or a gradient sublayer, and the thickness of each gradient layer is equal. The components of the gradient material change uniformly with the structure. Therefore, when the NC-SC functional gradient materials with different volume fractions are layered and combined, the weak area of ​​the interface can be eliminated and the interlayer strain can be coordinated. At the same time, the NC-SC functional gradient material still has the high ductility and crack control ability of SC, so that the material is fully utilized, the waste of resources is avoided, and a large amount of cost is saved.

[0009] The method for preparing the above-mentioned NC-SC functional gradient compressive material without interface damage comprises the following steps:

[0010] Step 1: Determine the relationship between the total number of layers of the NC-SC functionally gradient compressive material and the position of each layer;

[0011] Step 2: Determine the volume fraction of SC materials corresponding to different gradient layers;

[0012] Step 3: Cast in a layered manner to obtain a NC-SC functional gradient compressive material with an interface that is not damaged.

[0013] On the basis of the above technical solution, the present invention can also be improved as follows:

[0014] Furthermore, the relationship between the total number of layers of the NC-SC functionally gradient compressive material and the position of each layer is determined by the following formula:

[0015]

[0016] Where, k is the kth layer of the NC-SC functional gradient compressive material; n is the total number of layers of the NC-SC functional gradient compressive material, n≥5; z kis the center coordinate value of the z-axis thickness of the kth layer of NC-SC functional gradient compressive material, and the center position of the total thickness of the NC-SC functional gradient compressive material is the origin of the z-axis; d is the thickness of each gradient layer in the NC-SC functional gradient compressive material, in mm.

[0017] Furthermore, the volume fractions of SC in different gradient layers are graded according to an exponential function, and the volume fractions corresponding to different gradient layers are calculated.

[0018] Furthermore, the exponential function V(z k )for:

[0019]

[0020] Where V is the volume fraction of SC in the material; k is the kth layer of the NC-SC functional gradient compressive material; z k is the center coordinate value of the z-axis thickness of the k-th layer of NC-SC functional gradient compressive material, and the center position of the total thickness of the NC-SC functional gradient compressive material is the origin of the z-axis; v0 = 0.129; A = -0.22; e is a natural constant.

[0021] Furthermore, before layered pouring, the mold is slotted according to the required number of layers and matched with corresponding partitions.

[0022] Furthermore, when pouring in layers, pour in layers from the inside to the outside in sequence, with partitions between each layer. After the last initial setting, the corresponding partitions are removed to pour the next layer.

[0023] Furthermore, the mold is removed 24 hours after the pouring is completed, and then placed in a curing room for curing and solidification.

[0024] The present invention has the following beneficial effects:

[0025] The present invention provides a design method for NC-SC functional gradient compressive materials with no interface damage. The method aims at the problem that SC materials are expensive and that common composite materials are prone to interface damage. NC materials and SC materials are used as basic phases, and the two are compounded in different volume ratios, with the volume fraction of SC materials as the main component. The volume fraction of the SC material changes in a gradient to form different gradient layers. While NC-SC functional gradient materials with different volume fractions are layered and combined, weak interface areas can be eliminated and interlayer strains can be coordinated, so that the NC-SC functional gradient materials still have the high ductility and crack control ability of SC, making full use of materials, avoiding waste of resources, saving a lot of costs, and having broad application prospects in engineering construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1The coordinate division of the layers of 5-layer NC-SC functional gradient compressive material; among them, 11-partition, 21-the center coordinate z of the thickness in the z-axis direction.

[0027] Figure 2 This is a structural schematic diagram of the relationship between the number of layers of 5-layer NC-SC functional gradient compressive material and the position of each layer.

[0028] Figure 3 Schematic diagram of the mold structure.

[0029] Figure 4 This is a physical picture of the layered strain measurement of the compressive specimen.

[0030] Figure 5 The layered strain results of the compressive specimen of 5-layer NC-SC functionally gradient compressive material.

[0031] Figure 6 The cross-sectional layered strain results of NC-SC functionally graded compressive materials.

[0032] Figure 7 This is the compressive failure mode diagram of the NC-SC functional gradient compressive material prismatic specimen. DETAILED DESCRIPTION

[0033] The following examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] Embodiment 1:

[0035] A NC-SC functional gradient compressive material with no interface damage, the material is composed of multiple layers of NC-SC composite materials with the same thickness but different SC volume fractions in each layer and showing a gradient change, and the preparation method thereof comprises the following steps:

[0036] Step 1: Analyze the relationship between the number of gradient layers (or gradient sub-layers) and the position of each layer. Specifically, the position of the gradient layer is expressed by the axis coordinates, and the relationship between the number of gradient layers and the position of each layer is analyzed to obtain the relationship between the total number of layers of the NC-SC functional gradient compressive material and the position of each layer. The expression is as follows:

[0037]

[0038] Where, k is the kth layer of the NC-SC functional gradient compressive material; n is the total number of layers of the NC-SC functional gradient compressive material, n≥5; z kis the center coordinate value of the z-axis thickness of the kth layer of NC-SC functional gradient compressive material. The center position of the total thickness of the NC-SC functional gradient compressive material is the starting point of the z-axis, i.e., the origin; d is the thickness of each gradient layer, in mm.

[0039] Now, the calculation is performed by taking NC-SC functional gradient compressive material with 5 layers (the 1st layer, the 2nd layer, the 3rd layer, the 4th layer, and the 5th layer from top to bottom) as an example. The relationship between the total number of layers and the position of each layer is as follows (the structural diagram of the relationship between the number of layers and the position of each layer of 5-layer NC-SC functional gradient compressive material is shown in Figure 2 ):

[0040] Layer 1: z1 = -2d

[0041] Layer 2: z2 = -d

[0042] Layer 3: z3=0

[0043] Layer 4: z4=d

[0044] Layer 5: z5=2d

[0045] Step 2: The volume fraction of SC in the NC-SC functional gradient compressive material is calculated according to the exponential function V(z k ) to calculate the volume fractions corresponding to different gradient layers;

[0046] The expression of the exponential function is as follows:

[0047]

[0048] Where V is the volume fraction of SC in the material; k is the kth layer of the NC-SC functional gradient compressive material; z k is the center coordinate value of the z-axis thickness of the k-th layer of NC-SC functional gradient compressive material, and the center position of the total thickness of the NC-SC functional gradient compressive material is the origin of the z-axis; v0 = 0.129; A = -0.22; e is a natural constant.

[0049] Theoretically, the more gradient layers are subdivided, the smoother the performance gradient is and the better the functional gradient effect is. However, the NC-SC functional gradient compressive material studied in the present invention cannot be divided into too many layers like other metal ceramic materials, etc., considering the influence of the thickness of each layer. Therefore, the NC-SC functional gradient compressive material is calculated as 5 layers (from top to bottom, the first layer, the second layer, the third layer, the fourth layer, and the fifth layer) as an example. The design value of the volume fraction of each layer is shown in Table 1:

[0050] Table 1 Design values ​​of volume fraction of each layer

[0051]

[0052] It can be seen from Table 1 that the SC volume fractions of the five gradient samples from bottom to top are 100%, 86.889%, 68.135%, 41.556%, and 0, respectively.

[0053] Step 3: Taking the gradient layer as 5 layers as an example, the specimen mold is customized according to the required size, the mold is slotted according to the 5 layers, and equipped with corresponding partitions; the slot widths are equal, and the thickness of each gradient layer after the partition is inserted is evenly divided into the entire component width.

[0054] Step 4: Weigh the NC material and SC material respectively (the SC material in the present invention is the SMA-ECC cement-based composite material in the application number 201910267138.0, and the invention name is "A SMA-ECC cement-based composite material with self-healing cracks and its preparation method"), pour the NC dry material into the mixer and mix for 1 minute, then slowly add the corresponding amount of water and water reducer to the dry mix, stir for 3 minutes, until the mixed dry material forms NC slurry; stir the SC dry material such as polyvinyl alcohol (PVA) fiber, shape memory alloy (SMA), etc. for 3 minutes until the fiber is evenly distributed, then add the water reducer while stirring, mix and stir for 5 minutes to make the fiber fraction uniform, and form SC slurry. According to the volume fraction required for each gradient layer calculated in step 2, pour the NC slurry and SC slurry into the mixer and mix and stir for 3 minutes, so that the two materials are fully mixed and uniform, and form a mixed material with the required volume fraction for each gradient layer.

[0055] Step 5: Pour the mixed material into the mold, pouring in layers from the inside to the outside. Partitions are set between each layer. After the previous layer is initially solidified, the corresponding partitions are removed to pour the next layer. Each time the mold is injected, it is placed on a vibration table and vibrated for two minutes. After the vibration is completed, wait for the specimen to initially solidify, slowly pull out the partition, and smooth the surface of the specimen. The casting of the specimen is completed. After 24 hours of casting, the specimen is demolded and placed in a standard curing room (relative humidity of 90%, 20±2℃, 28 days) for curing and curing to obtain a 5-layer NC-SC functional gradient compressive material (also called a 5-layer functional gradient specimen). The coordinate division of each layer is shown in Figure 1 . Figure 1 11 is the partition, and 21 is the thickness center coordinate in the z-axis direction.

[0056] In order to verify the effectiveness of the functional gradient design theory mentioned above, the volume fraction of each gradient layer was obtained according to theoretical calculation, and the 5-layer NC-SC functional gradient compressive material was prepared in layers. The top layer of the functional gradient specimen was NC material, the bottom layer was SC material, and the middle layer was a NC-SC composite material transition layer mixed with different volume fractions of NC and SC. Because each group of functional gradient materials is prepared by layered casting, the mold for holding the functional gradient material slurry can no longer use an ordinary concrete mold. The mold required to hold the specimen slurry should be customized according to the size. The customized mold needs to be slotted in layers. According to the "Fiber Concrete Test Method Standard", the aspect ratio of the pressure mold is 3:1. At the same time, it is necessary to customize a partition of a certain thickness and size that meets the stiffness requirements to separate the layers of slurry so that the thickness of the second layer, the third layer, and the fourth layer are evenly divided across the entire specimen width. Before preparing the specimen, the surface of the customized mold and the partition are brushed with a layer of concrete release oil to facilitate the subsequent removal of the mold. The specific mold structure diagram is shown below. Figure 3 As shown ( Figure 3 Figure 3-2 is an enlarged view of the mold).

[0057] Test example

[0058] The NC-SC functional gradient compressive material prepared by the present invention was tested as follows:

[0059] The NC-SC functional gradient compressive material prism specimen with a size of 100 mm×100 mm×300 mm was subjected to compressive specimen layer strain measurement, and functional gradient compressive materials with the same size and 2, 3, and 4 gradient layers were subjected to compression as a control, and compared with the NC-SC functional gradient compressive material prepared in Example 1. The present invention verifies the superiority of the NC-SC functional gradient compressive material design method with no interface damage provided by the present invention from the perspective of the gradient specimen compressive failure mode and compressive layer strain.

[0060] 1. The actual picture of the layered strain measurement of the above-mentioned compressive specimen is shown in Figure 4 , the specific measurement method is as follows:

[0061] The cross-sectional strain detection of the NC-SC functional gradient compressive material prism specimens is carried out by attaching resistance strain gauges to the surface of each gradient layer (each sub-layer) of the functional gradient specimen. The resistance strain gauge is attached to the surface of each gradient layer of the functional gradient specimen, and the strain measurement direction is along the longitudinal direction of the specimen. The strain gauge should be attached to the middle part of each gradient layer and parallel to the specimen, and try not to be skewed to avoid measurement errors. The number of layers of each group of specimens is different, so the number of resistance strain gauges should correspond to the number of gradient layers of the specimen, and the resistance strain gauges of each layer are numbered for easy observation and recording. For example, for a 5-layer NC-SC functional gradient compressive material compression specimen, resistance strain gauges are attached to all five gradient layers, and the numbers are #1, #2, #3, #4, and #5 from the tensile side to the compressive side. The resistance strain gauge numbers of the NC-SC functional gradient compressive material compression specimen can be arranged in order.

[0062] Data recording: For the layered strain of the compressive specimen, when the load is loaded to a certain value, keep this state until the strain of each layer is stable and record the data. The cracking trend of the compressive specimen is analyzed and verified by the strain difference between each layer.

[0063] The delamination strain results of the 5-layer NC-SC functionally gradient compressive material compressive specimen are shown in Figure 5 ,Depend on Figure 5 It can be seen that in the 5-layer NC-SC functional gradient compressive material compression test specimen group, although there are 200 microstrains between the maximum strain layer and the minimum strain layer, the strain difference between each group is small, and the strain between layers has a coordinated effect. Therefore, when the 5-layer NC-SC functional gradient compressive material compression test specimen is damaged, cracks appear randomly and there is no interface damage. When the NC-SC functional gradient compressive material compression test specimen is set with 5 gradient layers, the gradient function effect can be fully exerted, so that the strain between each gradient sub-layer is coordinated, and the difference is reduced to 30-50 microstrains. Figure 6 The cross-sectional layered strain data of the bending specimens show that before the load level reaches 80% of the ultimate bearing capacity, the strain of each sub-layer changes linearly with the beam height, which basically meets the assumption of a flat section. When the load level is close to the ultimate bearing capacity of the functional gradient specimen under bending, the strain connection line of each sub-layer will be deflected, but the degree of deflection will not be too high. In general, the bending specimens of the NC-SC functional gradient compressive material still meet the assumption of a flat section.

[0064] 2. Analyze the failure mode of NC-SC functional gradient compressive material, specifically by applying pressure to the component to destroy it and observing the cross section of the specimen, including observation and recording of crack status, failure mode, etc.

[0065] The compression failure mode diagram of the NC-SC functionally graded compressive material prism specimen is shown in Figure 7 , Figure 7Figures 7-1, 7-2, 7-3, and 7-4 are respectively the compression failure mode diagrams of 2-layer, 3-layer, 4-layer, and 5-layer NC-SC functional gradient compression material prism specimens. Figure 7 It can be seen that the 2-layer, 3-layer, and 4-layer NC-SC functional gradient compressive material prism specimens all exhibit brittle failure when they are destroyed. After the load reaches the peak value, cracks on the surface of the specimens develop rapidly, and the crack width expands instantly. The curve at this stage also drops sharply. At the same time, the sound of fiber tearing or pulling out can be clearly heard. Finally, the main crack is formed and runs through the entire cross section, and the specimen is declared destroyed. Figure 7 It can be seen from 7-1, 7-2, and 7-3 that when the number of gradient layers is 2, 3, or 4, the main crack of the specimen during compression failure develops along the specimen delamination interface. When the number of gradient layers is set to 5, the main crack of the specimen is formed by Figure 7 As shown in Figure 7-4, when the specimen is under compression, the main crack does not develop along the interlayer interface as described above, but appears randomly on the surface of the specimen. The morphology and position of the crack are basically consistent with the phenomenon presented by the cement-based composite material (ECC) specimen under compression. This can be explained by the fact that when the number of gradient layers is set to be small, the performance difference between the layers of several gradient sub-layers is large, and the interface effect between the layers is very obvious. When the specimen is subjected to a load parallel to the interlayer interface, different deformations will occur between the layers, and there is a tendency to shift relative to each other, which makes the interlayer interface the weakest area of ​​the specimen, and the cracks will continue to develop and expand along the interface. When the gradient sublayer is increased to 5 layers, the surface layer of the NC-SC functional gradient compressive material is ordinary concrete and self-healing concrete, and there are three NC-SC composite material transition functional layers with different volume fractions in the middle. This makes the stress performance of these sublayers close to each other, and the deformation between the layers is mutually involved and coordinated, so that there will be no abrupt mutation in the interlayer deformation, which indirectly alleviates or even eliminates the interlayer interface effect. Therefore, there is no obvious interface effect when the 5-layer NC-SC functional gradient material is under pressure. At the same time, it can also prove the superior effect of introducing the functional gradient concept into cement-based materials.

[0066] In summary, compared with existing SC materials and ordinary composite materials, the NC-SC functional gradient compressive material provided by the present invention changes the disadvantage of damage in the weak interface area of ​​traditional materials, and has better mechanical properties required in engineering. In addition, Zhou Ya's test verified that 5 layers of NC-SC functional gradient compressive material do not cause interface damage, while interface damage will occur when the gradient sub-layers are less than 5 layers. Therefore, the gradient sub-layers of the NC-SC functional gradient compressive material are preferably greater than 5 layers to be effective.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A NC-SC functional gradient compressive material with no interface damage, characterized in that: include: NC material and SC material, the NC material and the SC material form different layers according to the gradient change of the volume fraction of the SC material, and the thickness of each layer is equal.

2. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 1, characterized in that: The following steps are involved: Step 1: Determine the relationship between the total number of layers of the NC-SC functionally gradient compressive material and the position of each layer; Step 2: Determine the volume fraction of SC materials corresponding to different gradient layers; Step 3: Cast in a layered manner to obtain a NC-SC functional gradient compressive material with an interface that is not damaged.

3. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 2, characterized in that: The relationship between the total number of layers of NC-SC functional gradient compressive material and the position of each layer is determined by the following formula: Where, k is the kth layer of the NC-SC functional gradient compressive material; n is the total number of layers of the NC-SC functional gradient compressive material, n≥5; z k is the center coordinate value of the z-axis thickness of the kth layer of NC-SC functional gradient compressive material, and the center position of the total thickness of the NC-SC functional gradient compressive material is the origin of the z-axis; d is the thickness of each gradient layer in the NC-SC functional gradient compressive material, in mm.

4. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 2, characterized in that: The volume fraction of SC in different gradient layers is graded according to an exponential function, and the volume fractions corresponding to different gradient layers are calculated.

5. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 4, characterized in that: Exponential function V(z k )for: Where V is the volume fraction of SC in the material; k is the kth layer of the NC-SC functional gradient compressive material; z k is the center coordinate value of the z-axis thickness of the k-th layer of NC-SC functional gradient compressive material, and the center position of the total thickness of the NC-SC functional gradient compressive material is the origin of the z-axis; v0 = 0.129; A = -0.22; e is a natural constant.

6. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 2, characterized in that: Before pouring in layers, the mold is slotted according to the required number of layers and matched with corresponding partitions.

7. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 2 or 6, characterized in that: When pouring in layers, pour in order from the inside to the outside, with partitions between each layer. After the last initial setting, remove the corresponding partitions to pour the next layer.

8. The method for preparing the NC-SC functional gradient compressive material with no interface damage according to claim 2, characterized in that: After pouring, demoulding is carried out 24 hours later and then placed in the curing room for curing and solidification.

Citation Information

Patent Citations

  • A self-healing SMA-ECC cement-based composite material for cracks and its preparation method

    CN109836102B